Asymmetrical DC bias analysis of the no‐load series transformer by using the TPFEM. Issue 2 (1st February 2017) - Wang, Shuaibing; Li, Lin; Zhao, Xiaojun; Xie, Yuqing; Cai, Linhai
Abstract : The time‐periodic finite element method (TPFEM) is coupled with circuit equations to study the asymmetrical DC bias problems of series transformer in this study. The periodic characteristics of the current and the magnetic field are taken as the restraint conditions. Taking into account the external voltages and determining the equivalent thickness of the two‐dimensional magnetic system by calculating the magnetic field energy, the field–circuit coupled time‐periodic finite element equations are built. The locally convergent fixed‐point method is used to solve the non‐linear time‐varying equations by updating the fixed reluctivity. The calculated results agree well with those measured on a no‐load low‐voltage series transformer prototype under asymmetrical DC bias, which verifies the effectiveness of TPFEM in the DC bias calculation. The characteristics of the no‐load series transformer prototype under asymmetrical DC bias are analysed based on this method.